Guanidinium Toxins and Their Interactions with Voltage-Gated Sodium Ion Channels - Durán-Riveroll, Lorena; Cembella, Allan (Marine drugs, 2017)
Guanidinium toxins, such as saxitoxin (STX), tetrodotoxin (TTX) and their analogs, are naturally occurring alkaloids with divergent evolutionary origins and biogeographical distribution, but which share the common chemical feature of guanidinium moieties. These guanidinium groups confer high biological activity with high affinity and ion flux blockage capacity for voltage-gated sodium channels (NaV). Members of the STX group, known collectively as paralytic shellfish toxins (PSTs), are produced among three genera of marine dinoflagellates and about a dozen genera of primarily freshwater or brackish water cyanobacteria. In contrast, toxins of the TTX group occur mainly in macrozoa, particularly among puffer fish, several species of marine invertebrates and a few terrestrial amphibians. In the case of TTX and analogs, most evidence suggests that symbiotic bacteria are the origin of the toxins, although endogenous biosynthesis independent from bacteria has not been excluded. The evolutionary origin of the biosynthetic genes for STX and analogs in dinoflagellates and cyanobacteria remains elusive. These highly potent molecules have been the subject of intensive research since the latter half of the past century; first to study the mode of action of their toxigenicity, and later as tools to characterize the role and structure of NaV channels, and finally as therapeutics. Their pharmacological activities have provided encouragement for their use as therapeutants for ion channel-related pathologies, such as pain control. The functional role in aquatic and terrestrial ecosystems for both groups of toxins is unproven, although plausible mechanisms of ion channel regulation and chemical defense are often invoked. Molecular approaches and the development of improved detection methods will yield deeper understanding of their physiological and ecological roles. This knowledge will facilitate their further biotechnological exploitation and point the way towards development of pharmaceuticals and therapeutic applications.